Megengan dalam menyambut bulan suci Ramdhan: Simbol harmoni budaya jawa dan spiritualitas Islam - Jamil, Dina Rahmatun Najma (Maliki Interdisciplinary Journal, 2025)
Indonesia is known as a country rich in culture and traditions, diverse from Sabang to Merauke. This diversity is closely related to the arrival of Islam, which was spread peacefully without coercion, blending with local cultures, particularly in Java. Islam Nusantara with its moderate and tolerant nature, has given birth to distincive local wisdom and pluralism. One form of cultural acculturation between Islam and Javanese culture is the Megengan tradition, a celebration welcoming the month of Ramadan with various rituals. This tradition reflects the fusion of Islamic religious values with local customs, making it an integral part of Javanese life. This study examines the Megengan tradition using a literature review method from various sources. The results show that this tradition holds significant meaning in Javanese society, such as asking for forgiveness, sharing with others, and preserving Islamic teachings. Megengan plays a role in strengthening social bonds and maintaining the spiritual balance of Javanese society. Overall, Megengan is a symbol of the successful acculturation of culture and religion in Indonesia, demonstrating how local tarditions and Islamic values can harmoniously unite, enriching Indonesia’s pluralistic cultural identity.